(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
During the weekend session of the Almirante Padilla School aimed at the education of young people and adults in the town 5 of Usme in Bogotá, the need arose to implement an educational system aimed at the 500th cycle of this student population. This need was detected thanks to the educational experience developed through the Universalizarte project; an educational project implemented in 2016 with the educational population of the weekend through the teaching of art history articulated with other educational areas of the school in a way transversal. Throughout this experience, the urgency of a special curriculum for the teaching of visual arts is diagnosed given the heterogeneity of the student population where young students and older adults demand a differential education in the teaching of visual arts that did not exist , according to the educational experience of the Universalizarte project at the Almirante Padilla school and other educational experiences investigated through interviews with teachers and coordinators of different schools in Bogotá with similar days. Thus, through the Universalize project of the Almirante Padilla School Weekend Day and research in other schools in Bogotá, a Special Curriculum for the teaching of the Visual arts of cycle 500 is achieved in the school that responds to the needs of the students. As well as occasional teachers on campus who have no notion of the teaching of visual arts and must teach it or wish to implement it in their pedagogical method.